The Role Of The Provided Service Quality In Achieving Customer Satisfaction (A Field Study On Citizen Service Centers In The City Of Lattakia) - سليطين , فاطر; اسماعيل , علي (Latakia University Journal - Economic and Legal Sciences Series, 2022)
The research aimed to present an image of the reality of the services provided in the citizen service centers in the city of Lattakia, and to study the impact of the quality of these services on customer satisfaction with them. The analytical descriptive approach was followed in this research by using the questionnaire method to collect primary data from a sample of 330 clients. The data was analyzed using the SPSS statistical analysis program.After the analysis, the following results were reached: The quality of services recorded average levels or less than average on the Likert scale used for all dimensions, except for the reliability dimension, which recorded a significant degree on the scale used. Satisfaction with the service provided was also average on the scale used, and the results of hypothesis testing showed a significant effect of the quality provided in its various dimensions on customer satisfaction.